Economic and Development Policy-Making in Nigeria - Ezeani, Elimma C (Journal of African law, 2012)
The difficulties in effective engagement with the global trade environment, especially given the rules-based system of world trade applicable to member states of the World Trade Organisation, are a constant subject for academic and political discourse, particularly when developing countries are involved. One consideration is however often overlooked: the internal constraints which must be faced in these countries along with their added obligations to comply with modern liberalization processes. This article studies these constraints by identifying the challenges facing one of sub-Saharan Africa's largest economies in constructing a stable legal framework for trade and development, which meets domestic needs and complies with the demands of the global market environment.